Delicaflavone Represses Lung Cancer Growth by Activating Antitumor Immune Response through N6-Methyladenosine Transferases and Oxidative Stress. (8th August 2022) - Wang, Xuewen; Xu, Dafen; Chen, Bing; Huang, Dandan; Li, Zhijun; Sui, Yuxia; Lin, Fei; Yao, Hong; Li, Huang Yuan; Lin, Xinhua
Abstract : Our previous studies have shown that delicaflavone (DLL), a biocomponent extracted from Selaginella doederleinii Hieron, has antitumor activity. However, the role of DLL in the antitumor immune response is unknown. In this study, we tested the potential roles of DLL in antitumor immune response. An animal tumor model with Lewis lung cancer cell line (3LL) in C57BL/6 mice was established to determine whether DLL induced the tumor-bearing host's antitumor immune response. m6A-MeRIP-qPCR, western blot, and flow cytometry were performed to explore the underlying mechanisms. DLL inhibited the proliferation of 3LL lung cancer cells in vitro and in vivo and induced tumor cell oxidative stress. DLL significantly inhibited tumor growth in immunocompetent mice compared with nude mice. DLL treatment significantly increased Th1 cytokine production and CD8+ T cell infiltration into tumor tissues in tumor-bearing mice. DLL-mediated antitumor immune effects were reversed by overexpression of the N6-methyladenosine (m6A) transferase Mettl3/Mettl14. Mechanistically, DLL upregulated the expression of Stat1 and Irf1 and the secretion of cytokines by inhibiting Mettl3 and Mettl14 in lung cancer cells. In conclusion, DLL inhibited lung cancer cell growth by suppressing Mettl3/Mettl14 to activate antitumor immunity. These findings provided an opportunity to enhance lung cancer immunotherapy.